Thiocyanate assisted performance enhancement of formamidinium based planar perovskite solar cells through a single one-step solution process. Issue 24 (31st May 2016) - Yang, Shida; Liu, Wenqing; Zuo, Lijian; Zhang, Xinqian; Ye, Tao; Chen, Jiehuan; Li, Chang-Zhi; Wu, Gang; Chen, Hongzheng
Abstract : Thiocyanate ammonium additives are found to improve the performance of FAPbI3 based planar perovskite solar cells through a single one-step method. Abstract : Thiocyanate ammonium (NH4 SCN) is introduced into the fabrication of formamidinium lead triiodide (FAPbI3 ) films through one-step spin-coating. The promoted formation of black trigonal phase α-FAPbI3 with better crystallinity has been observed after the addition of NH4 SCN, together with the supression of the formation of yellow hexagonal phase δ-FAPbI3 . Planar perovskite solar cells (PVSCs) based on NH4 SCN-assisted formed α-FAPbI3 films with high quality present a highest power conversion efficiency of 11.44% when 30 mol% NH4 SCN is applied. Notably, the addition of NH4 SCN is found to enhance the moisture stability of the perovskite. As a result, the planar PVSCs with 30 mol% NH4 SCN additive show improved stability under ambient conditions (RH: 30–40%) over those based on pristine FAPbI3 . NH4 SCN simultaneously enhances the efficiency and moisture stability of FAPbI3 based PVSCs through a single one-step solution method, facilitating their commercial fabrication and application.